Role of Religion in Social Change - Sarachandran, K (Journal of Dharma, 1984)
Generally our idea of religion labours under a misconception. By the word religion we think of an invisible realm of souls, gods and spirits. In the wider sense, religion consists of faiths and practices, prayers and incantations ceremonials and other observances of persons in relation to something divine. In a striater sense it symbolizes the spiritual urge, endeavour and final fulfilment of the soul's struggle for the manifestation and full realization of the divine in Man. Thus 'on the objective side, religion involves the recurring performance of certain human activities and thus belongs to the realm of external phenomena; on the subjective, it is a part of the hidden experience of the psychic life." I It is difficult to say whether the objective side or subjective side is more important. When thc purpose is to study religion in the context of social change the objective side may appear more important. Present-day sociologists however, argue that social change implies changes in the minds and ideas of man, and so the subjective side is also equally important.